2004
DOI: 10.1158/1078-0432.ccr-03-0806
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Histone Deacetylase Inhibitors FK228 and m-Carboxycinnamic Acid Bis-Hydroxamide with Proteasome Inhibitors PSI and PS-341 against Gastrointestinal Adenocarcinoma Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
6
35
0
2
Order By: Relevance
“…In vitro, depsipeptide induced p21 cip1 in several cell lines (30,36). Consistent with the p53 genotype, depsipeptide induced p21 cip1 in BT27 and IRS56 tumors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In vitro, depsipeptide induced p21 cip1 in several cell lines (30,36). Consistent with the p53 genotype, depsipeptide induced p21 cip1 in BT27 and IRS56 tumors.…”
Section: Discussionsupporting
confidence: 57%
“…However, determination of HDAC activity in the presence of inhibitor would be required to support such conjecture. In vitro, depsipeptide (5 nmol/L) increased histone acetylation after 24 hours in DLD-1 cells (30) and increased acetylation was due to inhibition of histone deacetylation, which was confirmed by determining the effects on HDAC activity (10,11). Therefore, the level of histones and histone acetylation state was investigated in tumors that were sensitive and insensitive to depsipeptide treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Anticancer compounds such as nanoparticles and chemotherapeutic agents cause malfunction of mitochondria, which in turn induce cell death in a variety of cancer cells. 34,40,57 Previously, several studies have suggested that a variety of chemotherapeutic agents such as HDACIs, 58 redox cycling agents, 59 proteasome inhibitors, 60 and silver and graphene nanoparticles induce oxidative stress in the cells and eventually lead to cell death. 34,48,61 To examine the change in intracellular ROS level caused by oxidative stress, SKOV3 cells were treated with rGO-Ag (0.20 µM) alone, TSA (0.20 µM) alone, or …”
Section: Rgo-tsa and Tsa Enhance Production Of Rosmentioning
confidence: 99%
“…12 Our earlier studies in pancreatic cancer models showed that disruption of aggresomes by genetic (siRNA) or pharmacologic (SAHA) inhibition of HDAC6 activity augments the anticancer activity of bortezomib. 10 The synergistic anticancer effects of simultaneous inhibition of HDACs and proteasomal activity have also been observed in other cancer models, [13][14][15][16] and this therapeutic strategy is now moving forward into clinical trials for advanced solid malignancies.The sensitivity to bortezomib and HDAC inhibitors such as SAHA relies upon active protein synthesis. 10,17 To identify patients who may most benefit from their clinical use, we further investigated what factors might regulate sensitivity to these agents.…”
mentioning
confidence: 91%